Synthesis and Evaluation of Water‐Soluble Prodrugs of Ursodeoxycholic Acid (UDCA), an Anti‐apoptotic Bile Acid. Issue 6 (2nd May 2013) - Dosa, Peter I.; Ward, Tim; Castro, Rui E.; Rodrigues, Cecília M. P.; Steer, Clifford J.
Abstract: Ursodeoxycholic acid (UDCA) is a bile acid with demonstrated anti‐apoptotic activity in both in vitro and in vivo models. However, its utility is hampered by limited aqueous solubility. As such, water‐soluble prodrugs of UDCA could have an advantage over the parent bile acid in indications where intravenous administration might be preferable, such as decreasing damage from stroke or acute kidney injury. Five phosphate prodrugs were synthesized, including one incorporating a novel phosphoryloxymethyl carboxylate (POMC) moiety. These prodrugs were highly water‐soluble, but showed significant differences in chemical stability, with oxymethylphosphate prodrugs being the most unstable. In a series of NMR experiments, the POMC prodrug was bioactivated to UDCA by alkaline phosphatase (AP) faster than a prodrug containing a phosphate directly attached to the alcohol at the 3‐position of UDCA. Both of these prodrugs showed significant anti‐apoptotic activity in a series of in vitro assays, although the POMC prodrug required the addition of AP for activity, while the other compound was active without exogenous AP. Abstract : Quick release: A series of water‐soluble prodrugs of the anti‐apoptotic bile acid UDCA were prepared, including a novel phosphoryloxymethyl carboxylate (POMC) prodrug. The POMC prodrug was bioactivated to UDCA by alkaline phosphatase more rapidly than a prodrug with a phosphate directly linked to an alcohol. Both of these prodrugs showed significant in vitro anti‐apoptotic activity.